The outcome of thrombolytic therapy for acute ischemic stroke after extended treatment from 3 to 4.5 hours in Maharaj Nakorn Chiang Mai Hospital - Watcharasaksilp, Kanokwan (Biomedical Sciences and Clinical Medicine, 2024)
Objective To present the outcome of acute ischemic stroke patients given thrombolytic therapy from 3 to 4.5 hours after the onset of symptoms. Methods All acute ischemic stroke (AIS) patients admitted to the Stroke Unit at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand and treated with tissue plasminogen activator (rtPA) between January 1, 2013, and December 31, 2013, were chart reviewed retrospectively. The recovery rate and complications were compared between patients treated within 3 hours and from 3 to 4.5 hours after the onset of symptoms (group A and B, respectively), as was the outcome between patients in Group B and those in Western trials. Results Ninety two AIS patients were treated with rtPA during the study period, with 68.48% and 31.52% of them being treated in Group A and B, respectively. Only the rate of neurological improvement was signifi cantly different at 24 hours between each group (55.0% vs 27.6%, p=0.03). There was no difference in favorable outcome at 3 months, including the rate of complete recovery (33.3% vs 51.7%, p =0.23) and functional independence (50.7% vs 58.6%, p =0.24). The complication of symptomatic intracranial hemorrhage (1.5% vs 3.4%, p=0.57) and mortality rate (at admission, 3.1% vs 10.3%, p=0.54 and at 3 months, 7.9% vs 10.3%, p=0.54) was similar. The outcome of patients treated in Group B was comparable to that from Western trials. Conclusion The outcome of patients treated in group B was comparable to that for patients treated in group A. The results of this study confirmed that the window of opportunity for rtPA treatment can extend to 4.5 hours. However, early rather than later treatment had a better outcome.